Ethnic Dermatology : Principles and Practice - Dadzie, Ophelia E.; Petit, Antoine; Alexis, Andrew F. (Wiley-Blackwell, 2013)
Richly pigmented skin is the most common skin type internationally Historically, dermatology has focused on white skin. But rich pigmentation can lead to differences in presentation, disease course and outcome, and reaction to treatment. Some dermatologic conditions are seen predominantly or only in richly pigmented skin. Ethnic Dermatology: Principles and Practice provides a practical approach to the dermatology of non-white skin. Written from a global perspective to include Asian, African-Caribbean and North African skin types, it covers all the bases of der.